Manejo da adubação nitrogenada para a cultura do feijão em sucessão a gramíneas forrageiras cultivadas para produção de sementes - Catuchi, Tiago Aranda [UNESP] (2015)
By maintaining residual straw on soil surface forage grasses grown for seed production changes in the dynamics of the soil nitrogen (N) may occur. Thus, common bean (Phaseolus vulgaris L.) growth in succession to these forage grasses with conventional N fertilizer recommendations, made in sidedressing, may have reduced grain yield by the lack of N, especially in the early stages of plant development. In this context, the practice of early N application on forage grass crop may increase the production of seeds of them and provide N in early common bean crop in succession, by providing straw production with smaller C/N. This also can contribute to decomposition of the straw mulch avoiding excessive accumulation in areas for the production of forage seeds, as high amounts of straw residues can disrupt the harvest, which is held on the ground after natural threshing. The objective of this study was to evaluate the effects of management of N fertilization on yield and quality of seeds of forage grasses (Urochloa humidicola cv. Llanero, U. brizantha cv. MG-5 and Panicum maximum cv. Mombasa), the decomposition of residual straw, and on nutrition and grain yield of common bean crop cultivated in succession, in no-tillage system under rates of N in. Three field experiments were conducted in forage seed production areas in the region of Presidente Prudente-SP, in the agricultural years 2012/13 and 2013/14. The experimental design was a randomized block in a split plot design, with four replications. The plots consisted of five forms of management of 150 kg ha-1 N in forage grass (0-0 (control), 150-0, 0-150, 100-50, and 50-100 kg ha-1 N ), approximately 40 days after the standardized harvest (Experiment I) or 40 days after emergence (DAE) (Experiment II and III) and pre-booting stage (floral differentiation)). The subplots were composed of N rates sidedressed to common bean ...